Egocentric biases and atypical generosity in autistic individuals. Issue 11 (17th May 2019) - Tei, Shisei; Fujino, Junya; Itahashi, Takashi; Aoki, Yuta; Ohta, Haruhisa; Kubota, Manabu; Hashimoto, Ryu‐ichiro; Nakamura, Motoaki; Kato, Nobumasa; Takahashi, Hidehiko
Abstract : Individuals with autism spectrum conditions (ASCs) often experience difficulty and confusion in acknowledging others' perspectives and arguably exhibit egocentricity. However, whether this egocentricity necessarily results in selfish behavior during social situations remains a matter of debate. To study this relationship, we used computerized visuospatial perspective‐taking task (VPT) and social‐discounting task (SDT), derived from cognitive psychology and behavioral economics, and examined egocentric and other‐oriented judgments in participants with ASCs (mean age 29.0 ± 4.2 years) and a group of matched typically developing (TD) controls (30.8 ± 8.5). The response time in VPT showed altered perspective‐taking in the ASCs group compared with the TD group that involved in enhanced self‐other intrusion and condition‐insensitive response. Regardless of self/other perspective judgments, responses were relatively slower and consistent in duration in the ASCs group compared with the TD group. Social discounting was attenuated rather than steep discounting in the ASCs group. Their discounting was comparatively more consistent, irrespective of the task condition (i.e., self‐other closeness‐level). In effect, ASCs group exhibited more generous decisions than the TD group in this task. Finally, those with more egocentric perspective intrusion in VPT paradoxically showed more generous behaviors in SDT in the ASCs group. Our findings suggest that having ASCs does not always exhibit selfish behavior during interpersonal communication. Reduced flexibility in distinguishing self/other perspective and shifting decision‐rules might account for this unique relationship between egocentricity and apparently generous behaviors. These results extend the recent suggestion that more careful attention should be paid to the idea of egocentricity in individuals with ASCs. Autism Res 2019 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: We aimed to examine whether seeing the world from another person's point of view and being generous toward other people are related in autistic and nonautistic people. We used a visual perspective‐taking task and a social task in which individuals made decisions about how to divide a sum of money with others. Our results suggest that being autistic does not always make someone bad at seeing the world from another's viewpoint, and that autistic people may make fairer social decisions toward unfamiliar people because of lower bias.